WORKSHOP TEKNIK MENENTUKAN RESEARCH GAP DAN NOVELTY UNTUK MENINGKATKAN KUALITAS SKRIPSI MAHASISWA - Hasnawati; Fitri Puji Astria; Muhammad erfan; Hikmah Ramdhani Putri (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2023)
Novelty is an important element in a study, including in student thesis research. However, the conditions in the field, the quality of student thesis is still lacking where the themes studied from time to time, from one generation to the next are almost the same and keep repeating, student skills in determining and selecting research themes that are new and relevant to current conditions still very low. It is rare to find elements of novelty and usefulness principles from the thesis research conducted. Students are often confused when asked about the novelty of the research they have done. Facing this, one of the initial solutions offered is to conduct a workshop on techniques for determining research gaps and the novelty of a study for students, especially 6th semester students who will propose topics or thesis titles. Reviewing various literatures to see research gaps from a major research theme will assist students in demonstrating elements of novelty or novelty from the research being conducted, thereby increasing the quality of the resulting thesis. This service activity certainly aims to provide knowledge and understanding to students about research gaps and novelty and how to determine techniques. The stages in this workshop activity are from the coordination stage, the promotion stage, the implementation stage as well as the evaluation and reporting stage. This workshop activity was carried out on Campus 2 of FKIP University of Mataram on May 27 2023. Based on the results of the pretest and posttest there was an increase in the understanding of the students participating in the workshop regarding the concept of research gap and novelty and based on the results of the participants' responses to the workshop activities carried out, the average student gave a positive response